Naruszewicz wśród Węgrów - Snopek, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The author of the article depicts an unknown chapter of the history of Adam Naruszewicz’s reception abroad in the age of Enlightenment. He presents two testimonies of the interest in the life and work of the eminent Polish historian and poet in the circles of Hungarian Enlightenment: a short biographical study written by János Molnár published in the magazine Magyar Könyvház and the correspondence of József Csehy, who planned to translate the poems of Naruszewicz but his too early and sudden death in the battlefield made it impossible for him to do so.